eNur: development of a digital laboratory management system with equipment loan features for nursing students - khasanah, Siti Nur; Suroso , Jebul; Purwito, Dedy; Hikmawati, Isna (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: The laboratory is essential in nursing education, where students develop practical skills using laboratory equipment. However, manual laboratory management often leads to issues such as inefficiencies in equipment borrowing, returns, and practicum scheduling, affecting the learning process’s smoothness. Purpose: This study aims to develop and test a digital laboratory management system with equipment lending features. Methods: This study uses Research and Development, which consists of four stages: Analysis Phase, application testing, Expert Validity, and Application Testing. Results: An eNur application, a web-based application using a computer with features for borrowing laboratory equipment and scheduling lab skills, has been created. Students can borrow lab equipment independently via smartphone. The results of the trial conducted on students found that this application system is more effective than manual. Conclusion: This application can improve the effectiveness and efficiency of laboratory management, especially in terms of borrowing, returning equipment and scheduling lab skill practicums. This application is user-friendly with an intuitive display and can be accessed anytime via computer or smartphone.